An Effective Compressed-Sensing Inspired Deterministic Algorithm for Sparse Array Synthesis - Pinchera, Daniele; Migliore, Marco Donald; Schettino, Fulvio; Lucido, Mario; Panariello, Gaetano (IEEE transactions on antennas and propagation, 2018)
The aim of this paper is to discuss a novel technique for sparse array synthesis. The synthesis strategy is based on a sparse-forcing algorithm using an improvement of the reweighted \ell _{1} minimization proposed in the framework of the compressed-sensing literature, specifically modified in order to tailor both linear and conformal array synthesis problems. The numerical examples show that the proposed algorithm improves the results provided by concurrent techniques, reducing the number of radiating elements and/or the computational effort.